KEANEKARAGAMAN JENIS BURUNG DIURNAL PADA KAWASAN HUTAN LINDUNG MANGROVE TELUK BESAR PARIT KELABU KABUPATEN KUBU RAYA KALIMANTAN BARAT - Purba, Riahma Delvirina; anto, Eri; Siahaan, Sarma (Universitas Tanjungpura, 2014)
This study aimed to determine the diversity of diurnal birds at Mangrove Bay Area Preserves Teluk Besar Parit Kelabu the of this research will provide data and information about the diversity of diurnal birds in the area, so it can be used as a basis in avian wildlife conservation efforts in the areal.The study was conducted at the Mangrove Bay Preserves Teluk Besar Parit Kelabu Kubu Raya regency of West Kalimantan, using the strip method combined with point count method.Broadband observations made ​​5 (five) placed randomly strip length of 200 meters with a bandwidth of observation 50 meters (25 meters to 25 meters left and right), with a path length of 200 meters. Where observation time that is in the morning starting at 5:30 to 7:30, daylight hours 13:00 to 14:30 and 16:30 to 18:00 o'clock afternoon.The results found 27 types of diurnal birds that are classified into 16 tribes (family).The composition of the bird species most often found in the morning is kind Gajahan East (Numenius madagascariensis) with a total of 65, the day of the East Gajahan (Numenius madagascariensis) with a total of 42, and the afternoon is Species diversity index, with the highest values​​ found in the morning with a value = 1.3467, based on the composition of insectivorous bird species feed as much as 23%, 44% fish eaters and fruit eaters / plant as much as 33%. The similarity index between path between 90.74% -100%. Keyword : Diversity, diurnal bird species, protecting mangrove forest